Pengaruh Pijat Bayi Terhadap Kualitas Menyusu Bayi - Siti Choirul Dwi Astuti; emi br barus (POLTEKKES KEMENKES MANADO, 2020)
Background : The coverage of exclusive breastfeeding among infants in North Sumatra in 2019 was 50.35% of the 333,285 babies. This indicated 30% the highest exclusive breastfeeding coverage in West Nusa Tenggara Province (Ministry of Health, 2019). Purpose: This study aims to identify the frequency and duration of breastfeeding before and after massage and its effects. Method: This was a Quasi-experimental study with pre-test and post-test design conducted to observe the effect of baby massage on the quality of infant breastfeeding. The quality of the infant breastfeeding referred to the frequency and duration of breastfeeding. Results: The analysis showed that there were 13 infants who experienced an increase in breastfeeding frequency. The Wilcoxon test result obtained a p value = 0.002. Thus, it can be concluded that Ha was accepted. Meanwhile, the duration of breastfeeding after baby massage increased among 14 infants. There were no infants who experienced a decrease in the duration of breastfeeding and there was one infant who did not experience a change in the duration of breastfeeding after baby massage. Wilcoxon test result obtained a p value = 0.001. Thus, it can be concluded that Ha was accepted and H0 was rejected. This indicated that there was an effect of baby massage on the frequency and duration of infant breastfeeding.